Theoretische Fundierung multiplen Sprachenlernens – Faktorenmodell 2.0 - Hufeisen, B. (2010)
The short article presents the "Faktorenmodell" (model of factors". It lists the different factors that play a role in acquiring or learning a L1, then a L2 and L3 (or Lx - meaning every language after). It assumes that there is a qualitative difference in learning a L3 as a lot of "foreign language learning factors" (e.g. language learning strategies) are acquired/added in the learning of a L2. (The qualitative difference between L2 and L3) was also shown in studies before and after). It has to be mentioned that for L2 and L3, the model is focusing on "learning" in an institutional context.